A systematic review of occurrence and concentrations of selected phthalic acid esters in waste processing and management facilities: Challenges and the future research perspectives - Fatemeh Momeniha; Hosna Janjani; Mina Aghaei; Mohammad Hadi Dehghani; Ali Salimifard; Suhas; Nabisab Mujawar Mubarak (Emerging Contaminants)
Municipal waste management and processing facilities produce various pollutants, including phthalic acid esters (PAEs), which are released into the environment depending on waste components, process type, and time elapsed. PAEs are widely used in industries, particularly in plastics, but their mismanagement poses risks to human health and the environment. The review aims to assess the levels of PAEs in different units of waste processing and management facilities and their health effects. This systematic review collected and analyzed studies investigating the levels of selected PAEs (DMP, DEP, DBP, BBP, DEHP, and DNOP) in waste processing and management facilities. The databases of Scopus, PubMed, and Web of Science were searched from the inception of the studies up to Oct 14, 2022. Studies were screened, duplicates removed, and relevant studies selected independently by two reviewers. Data from the final articles were extracted according to the study's objectives. A total of 26 studies were analyzed to assess the levels of PAEs, focusing on landfill leachate, soil, air, surface, and groundwater. The findings revealed that approximately 37 % of the studies were conducted in landfills, with DEHP having the highest concentration of PAEs. Moreover, all reviewed studies reported DEHP as the most prevalent PAE in leachate. Around 23 % of the studies were conducted on air and soil media, with DEHP, DBP, and DEP identified as the primary phthalates, comprising over 94 % of all the studied phthalates.The levels of PAEs in waste management facilities were often high, posing potential health risks to workers. Therefore, reducing plastic use and subsequently reducing waste generation should be considered as the priority action. Also, preventive measures such as dust control, personal protective equipment, and using anti-leak materials and membranes in waste processing and management sites should be implemented to reduce environmental pollution and human exposure.